Corrigendum to “Stability analysis and consistent solitary wave solutions for the reaction–diffusion regularized nonlinear model” (Results in Physics (2023) 54, (S221137972300846X), (10.1016/j.rinp.2023.107053)) - İnç, Mustafa; Alqahtani, Rubayyi T.; Sajid Iqbal, Muhammad (Elsevier B.V., 2024)
The authors regret to highlight a minor error in the affiliation of the second author. Specifically, a comma was mistakenly inserted after the word “Ibn” during the submission process and the same was published online. Below is the correct affiliation for Rubayyi T. Alqahtani: Department of Mathematics and Statistics, College of Science, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh 11432, Saudi Arabia. The authors extend their apologies for any inconvenience this may have caused. © 2024 The Author(s)